2020
DOI: 10.1371/journal.pgen.1008884
|View full text |Cite
|
Sign up to set email alerts
|

The membrane protein ANKH is crucial for bone mechanical performance by mediating cellular export of citrate and ATP

Abstract: The membrane protein ANKH was known to prevent pathological mineralization of joints and was thought to export pyrophosphate (PPi) from cells. This did not explain, however, the presence of ANKH in tissues, such as brain, blood vessels and muscle. We now report that in cultured cells ANKH exports ATP, rather than PPi, and, unexpectedly, also citrate as a prominent metabolite. The extracellular ATP is rapidly converted into PPi, explaining the role of ANKH in preventing ankylosis. Mice lacking functional Ank (A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 41 publications
3
79
0
Order By: Relevance
“…As citrate fails to go through the Krebs cycle within the matrix in these cells, it accumulates and gets transported out of the matrix into the cytoplasm via the citrate transporter SLC25A1 in the inner membrane, which occurs in exchange for malate (i.e., citrate enters the cytoplasm and malate enters the matrix). Once in the cytoplasm, citrate is released into the luminal space via pmCiC, an alternative splice variant of SLC25A1 (Mycielska et al, 2009;Mazurek et al, 2010) and most likely also via the recently described citrate exporter ANKH (SLC62A1) (Szeri et al, 2020). The metabolic phenotype of the normal prostate epithelium as a citrate producer is reversed upon transformation into cancer cells.…”
Section: The Pathways Supporting Mitochondrial Activity In Cancermentioning
confidence: 99%
“…As citrate fails to go through the Krebs cycle within the matrix in these cells, it accumulates and gets transported out of the matrix into the cytoplasm via the citrate transporter SLC25A1 in the inner membrane, which occurs in exchange for malate (i.e., citrate enters the cytoplasm and malate enters the matrix). Once in the cytoplasm, citrate is released into the luminal space via pmCiC, an alternative splice variant of SLC25A1 (Mycielska et al, 2009;Mazurek et al, 2010) and most likely also via the recently described citrate exporter ANKH (SLC62A1) (Szeri et al, 2020). The metabolic phenotype of the normal prostate epithelium as a citrate producer is reversed upon transformation into cancer cells.…”
Section: The Pathways Supporting Mitochondrial Activity In Cancermentioning
confidence: 99%
“…In particular, increased activation of the promineralizing bone morphogenetic protein 2 gene/protein (BMP2)–SMADs–RUNX family member 2 (RUNX2), TGF‐β2–SMAD2/3 and Wnt‐Msh homeobox 2 pathways was found. Further research into this topic revealed upregulation of other TGF‐β isoforms and associated downstream targets such as connective tissue growth factor, while a deficiency of progressive ankylosis protein homolog gene/protein (ANKH)—recently demonstrated to transport ATP and citrate—was also found [106,107]. The latter may partly contribute to the decreased PPi plasma levels observed in PXE patients, similar to what has been suggested for higher TNAP activity seen in PXE patients.…”
Section: The Human Abcc6 Genementioning
confidence: 80%
“…The question then arises as to the identity of the transport mechanism in the apical membrane that is responsible for the release of citrate from these cells onto the other side. The most likely candidate responsible for this process is the ANKH protein, which has been recently shown to function as a citrate transporter, releasing citrate from cells to the extracellular medium [ 110 ]. Interestingly, loss-of-function mutations or deletions of this transporter show severe defects in bone development, known as ankylosing spondylitis, both in humans and in mice [ 111 , 112 ].…”
Section: Nact In Bone Mineralization and Tooth Enamalization: Relevanmentioning
confidence: 99%